Effect of progesterone supplementation during mid luteal phase on conception in repeat breeder crossbred cows - AWASTHl, M K; TIWARl, R P; MISHRA, O P (The Indian Journal of Animal Reproduction, 2023)
Total 30 repeat breeder crossbred cows were selected for the present study. These cows failed to conceivewhen treated with post insemination intrauterine infusion of broad-spectrum antibiotic and with GnRH analogueon day ofinsemination. Single dose (500mg) bydroxyprogesterone caproate was administered 1:fM in the animalsof the treatment gr~p (n=20) between day 6 to 8 post insemination, following the confinnatJon of presence ofpresence of CL on one ovary. Treated animals exhibited significantly higher (0.05) conception rate compared tocontrol group (n= IO).
Keywords: Conception rate; progesterone; repeat breeder cows